Why study in Finland: RAMK, SAMK, and PBL - Khramtsova, Irina (Journal of International Students, 2011)
In September 2011, I visited two universities in Finland as part of Magellan faculty exchange: Rovaniemi University of Applied Sciences in Pori (RAMK) and Satakunta University of Applied Sciences in Pori and Rauma (SAMK). It was such a wonderful and rewarding trip that I decided to share my experience with students to encourage them to study abroad. to encourage them to study abroad. Arkansas State University is a member of Magellan Exchange Program (http://www.magellanexchange.org/). The mission of this program is “to provide opportunities for students and faculty to have an affordable educational and cultural immersion experience.” I decided to apply for this exchange to foster my professional development and to establish new contacts for cross-cultural collaboration in my area of research.